Bomb: The Race to Build - and Steal - The World's Most Dangerous Weapon - Sheinkin, Steve (New York : Roaring Brook Press, 2012)
Discusses the international competition to create the first atomic bomb.
Three-way race -- Chain reactions -- How to build an atomic bomb -- Final assembly -- Epilogue -- Race to trinity.
Includes bibliographical references (p. [243]-248) and index.
Keywords: Atomic bomb -- Juvenile literature. -- History; World War, 1939-1945 -- Juvenile literature. -- Secret service -- Soviet Union; World War, 1939-1945 -- Juvenile literature. -- Secret service -- Great Britain; World War, 1939-1945 -- Juvenile literature. -- Commando operations -- Norway; Operation Freshman, 1942 -- Juvenile literature; Atomic bomb -- Juvenile literature. -- History -- Germany; Atomic bomb -- History; World War, 1939-1945 -- Secret service -- Soviet Union; World War, 1939-1945 -- Secret service -- Great Britain; World War, 1939-1945 -- Commando operations -- Norway; Operation Freshman, 1942; Atomic bomb -- History -- Germany